Photonic signals and systems : an introduction - Riza, Nebeel A., 1962- (New York : McGraw-Hill, 2013)
'Build the skills needed to engineer next-generation systems using light Photonic Signals and Systems: An Introduction presents essential and current knowledge of light applied in the design of innovative photonic systems that engage both optical and electrical signals. The book demonstrates how to design photonic systems operating within the required approximations of the deployed photonic devices, mathematics of signal processing, and optical phenomena. Systems problems are solved using a variety of mature optical technologies, such as acousto-optics, liquid crystals, liquid optics, optical micro-electro-mechanical systems (MEMS), bulk optics, integrated optics, and optical fibers. End-of-chapter problems and solutions reinforce a thorough understanding of the material. Contents include: Nature of light Electromagnetic waves, light, and polarization Interference, coherence, and diffraction Optical building blocks--components Photonic systems using optical micro-electro-mechanical systems devices Photonic systems using acousto-optic devices Photonic systems using liquid crystal and liquid devices Optical experiments'--
'This entry-level undergraduate textbook empowers the next generation of engineering and science graduates with the skills to invent new systems using light'--
Includes bibliographical references and index.
Keywords: Signal processing; Optical communications; Photonics -- Industrial applications